The Republic, the Spanish Civil War and its impact on the Spanish community of Valparaíso - Estrada Turra, Baldomero (Revista de Historia Social y de las Mentalidades, 2025)
The evolution of the Spanish community of Valparaíso during the 1930s, when Spain was affected by the establishment of the Republic and later by the Civil War, is analyzed. The rupture that affected the Spanish community, as an effect of the events in Spain, was deeper than in other cities in the country and marked its institutional and community development for many years. Only the passing of the years and the generational changes made it possible to overcome the wounds of the past.
Keywords: Spanish community; civil war; republic; inmigration